2009
DOI: 10.1097/rli.0b013e3181a16762
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging Detects Intestinal Barrier Dysfunction in a Rat Model of Acute Mesenteric Ischemia/Reperfusion Injury

Abstract: This novel MRI-based intestinal permeability assay has shown a significant increase in the signal intensity in liver, kidney, and plasma samples that correlated with mucosal barrier defects in experimental models of acute mesenteric I/R.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 39 publications
2
25
0
Order By: Relevance
“…5,47 Here, we showed that rats preconditioned to a hypoxic environment displayed a significant reduction in bacterial counts in extraintestinal organs, associated with decreases in transepithelial macromolecular flux and mucosal histopathology on I/R challenge. The attenuation of BT may be attributed to higher barrier integrity and/or stronger antimicrobial effects of phagocytes.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…5,47 Here, we showed that rats preconditioned to a hypoxic environment displayed a significant reduction in bacterial counts in extraintestinal organs, associated with decreases in transepithelial macromolecular flux and mucosal histopathology on I/R challenge. The attenuation of BT may be attributed to higher barrier integrity and/or stronger antimicrobial effects of phagocytes.…”
Section: Discussionmentioning
confidence: 98%
“…These values in HPC-I/R rats were significantly lower than those of NM-I/R rats (Figures 3a and b). The real-time change of gut permeability in vivo was also assessed by portal drainage of enterally administered Gd using MRI techniques 47 ( Supplementary Figure 1). The Gd concentration in plasma samples of NM-I/R groups was significantly higher than that of NM-sham rats as early as 15 min after reperfusion, a condition that persisted up to 60 min (Figure 3c).…”
Section: Hpc Did Not Modulate Enteric Bacterial Numbers and Macromolementioning
confidence: 99%
See 2 more Smart Citations
“…30 In sham controls, gadodiamide was injected into the jejunal sac after mock manipulation. The rats were placed in a home-made resonance coil with inner diameter of 6 cm, and abdominal MRI was performed at various time points (0, 5, 10, 15, 30, 45, and 60 min) using a clinical 1.5T MR System (Signa Excite; GE Healthcare).…”
Section: Magnetic Resonance Imaging (Mri)-based Gut Permeability Assaymentioning
confidence: 99%